2021
DOI: 10.1103/physrevmaterials.5.073801
|View full text |Cite
|
Sign up to set email alerts
|

Finite-temperature interplay of structural stability, chemical complexity, and elastic properties of bcc multicomponent alloys from ab initio trained machine-learning potentials

Abstract: An active learning approach to train machine-learning interatomic potentials (moment tensor potentials) for multicomponent alloys to ab initio data is presented. Employing this approach, the disordered body-centered cubic (bcc) TiZrHfTa x system with varying Ta concentration is investigated via molecular dynamics simulations. Our results show a strong interplay between elastic properties and the structural ω phase stability, strongly affecting the mechanical properties. Based on these insights we systematicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 60 publications
(78 reference statements)
0
11
0
Order By: Relevance
“…There is also some promise in predicting mechanical properties from machine learning . MLIPs for high entropy alloys have been used to screen the temperature and composition dependence of elastic constants identifying alloys displaying invariable elasticity . Given the promise of these materials for applications such as thermoelectrics and ion conductors, enabling high-throughput calculations of electronic, thermal, and ionic transport properties is perhaps the most rewarding route.…”
Section: Discussionmentioning
confidence: 99%
“…There is also some promise in predicting mechanical properties from machine learning . MLIPs for high entropy alloys have been used to screen the temperature and composition dependence of elastic constants identifying alloys displaying invariable elasticity . Given the promise of these materials for applications such as thermoelectrics and ion conductors, enabling high-throughput calculations of electronic, thermal, and ionic transport properties is perhaps the most rewarding route.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the configurations obtained from MD simulations, they successfully separated the static, dynamic, thermal expansion, and chemical short-range order (CSRO) contributions to the LLD, as well as their impacts on the elastic properties. Gubaev et al [174] investigated the elastic constants of TiZrHfTa by chemically tuning the concentration of Ta, using MTP-informed MD simulations. They found that structural phase change can profoundly impact elastic properties.…”
Section: Molecular-dynamics Simulationsmentioning
confidence: 99%
“…To quantify the displacive phase transformation at the atomistic level, we introduce a structural descriptor ∆ along similar lines as done previously for materials showing the bcc-ω phase transformation [28][29][30]. The key requirements are as follows:…”
Section: B Structural Descriptor ∆mentioning
confidence: 99%